MAJOR GENERAL GEORGY ARANDARENKO: MILITARY AND STATESMAN, FIRST RESEARCHER BUKHARA KHANATE AND AFGHAN TURKESTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
For the first time, detailed biographical data on the military and administrativeservice of Major General Georgy Arandarenko (1846-1908), military governor and commanderof the Fergana region of the Turkestan Governor-General, an outstanding scientist and statesmanof the Russian Empire in the second half of the XIX century, one of the first researchers of theBukhara Khanate and Afghan Turkestan. The data on his ancient Polish gentry origin from theYaranda clan of the Brudze coat of arms of Pomyan, about his Zaporozhye ancestors, whose famousИзвестия НАН КР, 2021, № 1 73representatives were the Cossack hetmans Timofey Arandarenko and Taras Shakilo are given. Hisscientific, ethnographic and statistical studies of Gissar, Karatygin, Darvaz, the eastern part of theBukhara Khanate, winter trips to the glaciers of Zaravshan are considered. The stages of G.A.Arandarenko’s service in Turkestan, his powers and reasons for resignation are discussed in detail.A comprehensive analysis of his personality and contribution to the conquest and administrationof Turkestan is given.
Keywords: Georgy Arandarenko, Jarand z Grabi i Brudzewa h. Pomian, Central Asia, Bukhara Khanate, Afghan Turkestan, Darvaz and Karategin, military administration, power elite, administration, geographic and ethnographic research, journalism.